Design of smart hospital bed for stroke patient with linear actuator motor - Suharto Suharto; Totok Prasetyo; Eko Saputra; Moch. Muqorrobin; Wafa Umrotu Sihab (UJoST- Universal Journal of Science and Technology, 2022)
Improving services for patients is a hospital need. Stroke patients have limitations in the movement of body parts that cannot be controlled. It is caused by vascular disease and brain damage. Stroke patients need special services with electronic beds. The need for electric beds in hospitals can be an effective solution to provide complete patient care services. Manual bed in the hospital that is used to change the patient's position by hand using a crank. The electric bed is designed with an electric motor prime mover equipped with a control system. The purpose of this study is to design an electric hospital bed for stroke patients that can be used to improve patient care. The research method begins with a preliminary study which includes field studies and literature studies. The next stage is the design stage, the manufacturing stage, the purchase of standard components such as the electric linear actuator, the assembly stage, and the smart hospital bed performance testing stage. The results of this study are a smart hospital bed unit with dimensions of 2000×900×600 mm, has an electric linear actuator with a constant speed of 20 mm/s. The smart hospital bed movement test was successfully carried out with a remote control. The test parameters used were the patient's weight in 5 movements, back movement, left leg movement, right leg movement, body tilting movement to the left, and body tilting movement to the right. Smart hospital bed innovation can improve medical personnel services for stroke patients in hospitals.